Formation of production cost by the methods of “Target costing” and “Kaizen costing” and their impact on the enterprise efficiency - Pererva, Petro; Chernyshenko, Olena; Ponomarov, Vladyslav; Kobielieva, Tetiana; Veresne, Somosi M.; Nagy, Szabolcs; Keršys, Robertas; Reichling, Peter; Tkachova, Nadiya; Tkachov, Maksym (Technology audit and production reserves, 2025)
The object of this research is the process of formation of costs of enterprises for the production and sale of industrial products. The need for such a study is determined by the use of outdated methods of forming the cost of production at Ukrainian industrial enterprises, which are based on the actual costs of the enterprise. It is proved that the existing provisions of direct costing do not reproduce the provisions of the market pricing mechanism, since the market price is focused not on actual costs, but on the needs and preferences of consumers of products. A detailed study of the existing methods of forming the cost of production was carried out, among which special attention was paid to modern methods of target costing and kaizen costing, developed and widely tested by economists of Japanese enterprises. The main advantages of target costing and kaizen costing systems when they are used in the conditions of the Ukrainian economy are studied and substantiated. The systems proposed for use provide for putting in the first place not the actual costs, but the market price of the product, and the costs are formed taking into account the desired level of profit for the enterprise. This approach involves the integral (complex) use of target costing and kaizen costing. It has been proven that the combination of these two systems allows to create a continuous cycle of production cost management at all stages of the product life cycle. Target costing provides strategic cost control during the product design phase, while kaizen costing supports and increases efficiency during the production and operation phase. The combination of targeted costing and kaizen costing provides a significant increase in the efficiency of industrial enterprises, is an effective way to achieve strategic and operational goals, increase the competitiveness and sustainable development of industrial enterprises. This is achieved due to the complementarity of these systems at different stages of the product life cycle.